Biopolymer based carbon nanocomposite for the electrochemical determination of selected painkiller drugs / Md.Shalauddin - Md., Shalauddin (2021)
Biopolymers are naturally occurring polymers which have attained profound interest and are investigated widely due to their outstanding characteristics and several advantages such as cost efficiency, excellent hydrophilicity, film formation capability, chemical inertness, non-toxicity, high mechanical integrity and biocompatibility. Cellulose and chitosan are the two most abundant biopolymers in the world. Recently, the incorporation of nanocellulose and chitosan into electroconductive platform i.e nanostructured carbon such as- multiwall carbon nanotube (MWCNT) and nitrogen doped graphene (NDG) is the focus of this thesis for the fabrication of modified electrodes as electrochemical sensor for the detection of some common painkiller drugs. Nanocellulose (NC) and chitosan (CTS) possess excellent properties such as biocompatibility, non-toxicity, biodegradability, film formability, dispersion of nanomaterials and preventing leaching of nanomaterials. These biopolymers enhance the electrocatalytic activity of the carbon-based nanoparticles for the sensitive determination of commonly administered painkillers. Multiwall carbon nanotubes and nitrogen doped graphene both are nanostructured carbons and possess excellent features such as high dispersion, chemical and mechanical stability, high electrical conductivity, high surface area etc. These two nanomaterials are conducting scaffold in the presence of biopolymers for the homogenous dispersion of nanomaterials and ultimately enhances the electrons transfer process. A hybrid nanocomposite of NC and MWCNT was prepared, where NC was synthesized while the MWCNT was functionalized by acid hydrolysis method to afford the f-MWCNTs/NC/GCE for the electrochemical determination of widely used painkiller drug, iv diclofenac sodium. The assimilation of NC and f-MWCNTs enhances the active surface area by proper dispersion of the nanomaterials which enhances the electrical conductivity, accelerates the electrons transfer rate and ultimately amplifies the electrochemical response towards the determination of the targeted analyte. While a nanocomposite comprising of nitrogen doped graphene (NDG), nanocellulose (NC) and sodium dodecyl sulphate (SDS) i.e (NDG-NC)-SDS was prepared for the simultaneous determination of two common painkillers paracetamol (PCT) and naproxen (NPX) in the presence of another painkiller, diclofenac sodium (DCF). Due to binding property of NC, the junction of NC with NDG establishes a good bonding with each other and could be embedded into the graphene nanosheets. Another nanocomposite composed of MWCNT, CTS and copper (Cu), f-MWCNTs/CTS-Cu was prepared for the determination of DCF. The excellent catalytic effect of f-MWCNTs, adsorption capacity and film formation ability of CTS and the incorporation of Cu by immobilization technique enhances the catalytic effect of CTS-Cu complex. The fabricated f-MWCNTs/CTS-Cu nanocomposite is a potential candidate for the analytical detection of DCF. While another conductive biopolymer nanocomposite containing NC and conductive polymer polypyrrole (PPY) was prepared for the simultaneous determination of paracetamol (PCT) and ciprofloxacin (CPR) in commercial dosage forms, biological media and water sample. It should be mentioned that the synthesized biopolymer based nanostructured carbon nanocomposite have been fabricated for the first time for the detection of some common used painkiller drugs in commercial dosage forms and biological fluids.